Revision of the Advanced Cancer Patients’ Distress Scale (ACPDS): a mixed-methods study among palliative patients and healthcare professionals in Germany - Züger, Andrea; Fischbeck, Sabine; Weber, Martin; Mai, Sandra (BMJ open, 2023)
Objectives: To revise the 37-item Advanced Cancer Patients’ Distress Scale (ACPDS) regarding its content, comprehensibility, applicability, and relevance by healthcare professionals (HCPs) and patients in order to enhance an existing instrument that is appropriate for the needs of patients with advanced cancer admitted to palliative care. - Design: A preliminary revision of items regarding psychometric indices and relevance to initially shorten the scale, complemented by cognitive interviews with patients combining think-aloud and verbal-probe techniques and an HCP focus group on the detected remaining items. Interviews and the focus group were audio-recorded, transcribed verbatim and analysed using MAXQDA. - Setting: The study took place at a German palliative care unit. - Participants: 10 patients were interviewed (50% female) and 6 HCPs (3 physicians, 2 nurses and 1 psychologist) participated in the focus group. - Outcome Measures: Comprehensibility, applicability, and relevance of the ACPDS were evaluated. - Results: Based on the psychometric revision, a reduced number of 17 items was discussed by the HCP focus group and within cognitive interviews with patients. For the rest of the analysis of the HCP focus group and the patient interview data, the introduction of the ACPDS was simplified and adapted to everyday language. As recommended by HCPs and patients, the example question was replaced. Nine items were reworded to boost clarity, openness, redundancy and mitigation. Three items were eliminated, and another three items were added. - Conclusion: With this revised 17-item version of the ACPDS, we constructed an instrument that seems to be appropriate for the needs of patients with advanced cancer in a palliative care setting. In the next step, the shortened scale will be tested on psychometric data and validated by a large sample of inpatients on palliative care suffering from advanced cancer. - Trial registration number DRKS ID: DRKS00022425.